De marginales y elecciones : una aproximación a las restricciones al derecho al voto de los condenados - Scarramberg, Juan Martín (2018)
This paper will analyze the existing restrictions on the right to vote of people who have been convicted. Although the electoral justice has declared unconstitutional these limitations, reality shows that progress has not yet been made in order to guarantee the effective exercise of the right. Legislative neglect and judicial abandon are the perfect combo for it. The article tries to insert these restrictions within a larger set, marked by the systematic violations of the rights of the inmates, and to give the guideline that advancing in these reparations constitutes a debt of our democracy.